MODEL PERCEIVED SOCIAL SUPPORT PEREMPUAN KADER SURABAYA HEBAT DALAM PENURUNAN PREVALENSI STUNTING - Puspitasari, Sendy Krisna; Andriyanto, Andriyanto (EGALITA, 2024)
Abstract Stunting is a health problem in children due to chronic malnutrition that has a negative impact. Reducing the prevalence of stunting is a commitment of Kader Surabaya Hebat (KSH) women by prioritizing perceived social support. The role of KSH women as the leading sector in reducing the prevalence of stunting is evident in this study. This study aims to explore the model and process of perceived social support in the role of KSH women in the community. KSH women are also the main focus of the research and how the model becomes a modality of character building in Surabaya City. This research uses descriptive qualitative methods through observation and interviews. The results showed that the perceived social support model applied by KSH women is emotional support, instrumental support, information support, appreciation support, and social network support. The process of perceived social support starts from face-to-face dialogue, building trust, commitment to the process, sharing understanding, and temporary results that are carried out have gone well and are effective in reducing the prevalence of stunting in Surabaya City. . Keywords: Kader Surabaya Hebat Women; Stunting; Perceived Social SupportAbstrak Stunting merupakan permasalahan kesehatan pada anak akibat malnutrisi kronis yang berdampak buruk. Penurunan prevalensi stunting menjadi komitmen perempuan Kader Surabaya Hebat (KSH) dengan mengutamakan perceived social support. Peran perempuan KSH menjadi leading sector dalam penurunan prevalensi stunting terbukti pada penelitian ini. Penelitian ini bertujuan untuk mengeksplorasi model dan proses perceived social support dalam peran perempuan KSH di masyarakat. Perempuan KSH juga menjadi fokus utama penelitian serta bagaimana model tersebut menjadi satu modalitas pembangunan karakter di Kota Surabaya. Penelitian ini menggunakan metode kualitatif deskriptif melalui observasi dan wawancara. Hasil penelitian menunjukkan bahwa model perceived social support yang diterapkan perempuan KSH adalah dukungan emosional, dukungan instrumental, dukungan informasi, dukungan apresiasi, dan dukungan jaringan sosial. Proses perceived social support dimulai dari dialog tatap muka, membangun kepercayaan, komitmen terhadap proses, berbagi pemahaman, dan hasil sementara yang dilakukan sudah berjalan baik dan efektif dalam penurunan prevalensi stunting di Kota Surabaya.  Kata Kunci: Perempuan Kader Surabaya Hebat; Stunting; Perceived Social Support